Ceramic core for reducing recrystallization of inner cavity of single crystal blade and preparation method
By using ceramic inner core made of calcium silicate, quartz glass powder and cubic quartz powder, combined with sintering and impregnation reinforcement treatment, the problem of recrystallization in the inner cavity of the single crystal high-temperature alloy turbine blade is solved, and the recrystallization is achieved. The effect of the blade improves the high temperature resistance and pass rate.
Patent Information
- Application Number
- CN202411509963.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-27
AI Technical Summary
The residual stress caused by the difference in thermal expansion coefficient between the ceramic core and the metal during cooling process of single crystal high-temperature alloy turbine blades leads to recrystallization of the inner cavity, affecting the high-temperature resistance and pass rate of the blades. The existing prevention and control measures are not effective .
The ceramic inner core made of calcium silicate, quartz glass powder and cubic quartz powder is prepared by hot pressing, dry press forming or extrusion forming process, combined with sintering and impregnating reinforcement treatment, and designed with elongated rod or The sheet-shaped ceramic core is used to reduce the recrystallization of the inner cavity, and the ceramic inner core is used in conjunction with the outer core to control the recrystallization position.
It effectively reduces the possibility of recrystallization in the cavity of a single crystal blade, improves the mechanical strength and durability of the ceramic core, improves the pass rate and service performance of the blade, and has a simple process and a low cost.
Smart Images

Figure CN119187440A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of aero-engine blade casting, and in particular to a ceramic core for reducing recrystallization in an inner cavity of a single-crystal blade and a preparation method thereof. Background Art
[0002] As the "heart" of an aircraft, the research and development of an aircraft engine directly affects the development of the aviation industry. Among them, turbine blades are one of the core components of aircraft engines, and their operating temperature determines the thrust-to-weight ratio of the engine. Nickel-based single crystal high-temperature alloys are widely used in advanced aviation gas turbine blades due to their excellent high-temperature performance. However, turbine blades are subjected to complex aerodynamic thermal and mechanical loads, and the working conditions are extremely harsh. Therefore, it is particularly necessary to further improve the high-temperature resistance of the blades.
[0003] In order to improve the high temperature resistance of the blade, an efficient cooling design with a complex cavity hollow structure can be adopted. However, this design has poor compatibility with single crystal high temperature alloys. When the hollow blade has an air cooling channel inside, the turbine blade is usually manufactured by a casting process. During the cooling process of casting, due to the different thermal expansion coefficients of the metal and ceramic cores and the complex internal structure of the blade, the shrinkage of the alloy during cooling will be hindered by the core, resulting in large casting residual stress inside the blade. The main source of residual stress is that the alloy is constrained by the core during cooling and shrinkage. Therefore, the yieldability of the core determines the magnitude of residual stress during the casting process. A core with good yieldability can effectively reduce the residual stress in single crystal blades and avoid recrystallization of the inner cavity of the blade during heat treatment, which is of great significance for engineering practice.
[0004] Single crystal high temperature alloys are very sensitive to recrystallization due to the lack of or low content of grain boundary strengthening elements. Once recrystallization occurs in a certain area of a single crystal blade, cracks are likely to occur at the interface between the recrystallized area and the matrix, eventually leading to blade breakage and causing serious economic losses. Therefore, the key parts of turbine blades have extremely high requirements, especially the inner cavity of the blade, where recrystallization is almost not allowed. However, the recrystallization phenomenon in the inner cavity can only be discovered through anatomical analysis, which makes the yield of the ceramic core crucial to the qualification rate and service performance of single crystal turbine blades.
[0005] At present, many studies have tried to control the recrystallization of single crystal high-temperature alloys by using methods such as recovery heat treatment, carburizing, and surface corrosion. However, these methods have limited control effects on the recrystallization of the inner cavity, especially the surface corrosion method may damage other non-recrystallized areas of the blade, resulting in irreversible surface damage.
[0006] With the increasing complexity of the blade cavity structure or the emergence of new ceramic core designs, the requirements for core yield are further increased. Traditional recrystallization prevention and control measures are not effective. Relying on changing the overall casting process or ceramic core material not only reduces the process performance, but also affects the qualified rate of the blade.
[0007] Therefore, it is particularly important to design a ceramic core that can effectively reduce the recrystallization of the inner cavity of the single crystal blade. Summary of the invention
[0008] The object of the present invention is to provide a ceramic core material and a manufacturing method for preventing the inner cavity recrystallization of a single crystal high-temperature alloy hollow turbine blade, so as to solve the problem of inner cavity recrystallization and accurately handle recrystallization.
[0009] In order to achieve the above object, the technical solution of the present invention is as follows:
[0010] A powder material can be used to prepare a ceramic inner core. The powder material comprises calcium silicate, quartz glass powder and cristobalite, and the mass ratio thereof is (1.0-8.0): (20-66.5): (15-30).
[0011] Furthermore, the powder includes 500-600 mesh calcium silicate, 325-350 mesh quartz glass powder and 150-200 mesh quartz.
[0012] Furthermore, the powder includes 600 mesh calcium silicate, 325 mesh quartz glass powder and 200 mesh cristobalite.
[0013] Furthermore, the mass ratio of the calcium silicate, quartz glass powder and cristobalite is (2.0-6.0):(30-40):(20-25).
[0014] Furthermore, the optimal solution is that the mass ratio of calcium silicate, quartz glass powder and cristobalite is 1.0:66.5:30.
[0015] A ceramic core for reducing recrystallization in the inner cavity of a single crystal blade, made from the powder material mentioned above.
[0016] Furthermore, the ceramic inner core is: a slender rod-shaped ceramic inner core with a diameter of 0.5-2 mm, or a sheet-shaped ceramic inner core with a thickness of 0.5-2 mm.
[0017] A method for preparing a ceramic core for reducing recrystallization of a single crystal blade cavity comprises the following steps:
[0018] The powder is mixed with an additive, an appropriate amount of water is added, and the mixture is ground to obtain a mixed slurry, wherein the additive includes a plasticizer;
[0019] The mixed slurry is formed into a ceramic core blank, and the forming method includes: hot pressing method, dry pressing method, and extrusion molding method;
[0020] Sintering the ceramic inner core blank to obtain a sintered ceramic inner core blank;
[0021] The sintered ceramic core blank is immersed in a reinforcing agent and then dried to obtain a ceramic core.
[0022] Furthermore, the additive also includes paraffin.
[0023] Further, the green embryo is sintered in an air environment, and the sintering process is: heating from room temperature to 1000-1450° C., and maintaining the temperature for 3-8 hours.
[0024] The present invention also protects a ceramic core for reducing recrystallization in the inner cavity of a single crystal blade. The ceramic core includes the above-mentioned ceramic inner core or the ceramic inner core obtained by the above-mentioned preparation method, and an external core compatible with the ceramic inner core.
[0025] Furthermore, the outer core is provided with a hole for placing the ceramic inner core, and the distance between the recrystallization position of the ceramic inner core and the outer core is adapted to the size of the ceramic inner core;
[0026] The diameter or thickness of the ceramic inner core is 0.5-2 mm, and the distance between the ceramic inner core and the corresponding blades of the outer core is 1-5 mm.
[0027] The present invention also provides a ceramic core material and preparation method for preventing recrystallization of the inner cavity of a single crystal blade, wherein the ceramic core is composed of an outer core and an inner core; wherein the inner core is a slender rod-shaped or sheet-shaped structure with a diameter or thickness of 0.5-2 mm, and can be prepared by hot pressing or dry pressing. The ceramic inner core is embedded in the outer core 1-5 mm from the position where the blade appears to recrystallize, and the position where the blade appears to recrystallize is the contact position between the outer core and the blade, and the specific distance is determined according to the diameter or thickness of the ceramic inner core; the materials of the ceramic inner core each account for 1.0-8.0 wt% of 600 mesh calcium silicate, 20-60 wt% of 325 mesh quartz glass powder, 15-30 wt% of 200 mesh quartz, 0.5-1.0% of PVA plasticizer or 1-2% of paraffin wax.
[0028] The preparation process of the ceramic core includes the following specific steps:
[0029] 1) Mixing and ball milling: First, the powder materials are mixed according to the proportion. The purpose of this step is to ensure that the various components are evenly distributed. After mixing, they are passed through a ball mill for ball milling to obtain a uniform mixed slurry;
[0030] 2) Molding process: prepare the slurry after ball milling, select a suitable molding method, such as hot pressing, dry pressing or extrusion molding, and use a special mold to prepare a slender rod-shaped or sheet-shaped blank with a diameter or thickness of 0.5-2.0 mm;
[0031] 3) Sintering treatment: Place the formed ceramic core in high-purity alumina powder for sintering. The sintering process requires slowly heating from room temperature to 1000-1450°C and maintaining this temperature for 3-8 hours;
[0032] 4) Impregnation and drying: Finally, the sintered ceramic core is immersed in the prepared reinforcing agent resin solution. This step enhances the mechanical strength and durability of the ceramic core through the penetration of the resin. After impregnation, the ceramic core needs to be thoroughly dried to ensure that all solvents are completely volatilized and the resin is fully hardened, thereby forming the final high-performance ceramic core that meets the application requirements.
[0033] A ceramic core for reducing recrystallization in a single crystal blade cavity and a preparation method thereof, the preparation method specifically comprising the following steps:
[0034] 1) The external core is prepared by hot injection molding process. During the preparation process, a needle with a diameter or thickness of 0.5-2 mm is set at the corresponding recrystallization position 1-5 mm in the molding mold, and then a sheet is drawn, and the pressing is completed to form an external core with a hole;
[0035] 2) The ceramic inner core is embedded in the hole reserved for the outer core, and then the alumina or silicon oxide ceramic rod is filled to seal the hole. The port position is repaired with a high-temperature adhesive. The distance between the recrystallization position of the ceramic inner core and the outer core needs to be strictly controlled and determined according to the size of the ceramic inner core. The preferred distance is 1-5 mm.
[0036] The ceramic core and preparation method for reducing recrystallization in the inner cavity of a single crystal blade described in the present invention utilize the characteristics of the ceramic core having a low melting point and softening at high temperature to specifically weaken the locations in the inner cavity of the turbine blade where recrystallization is likely to occur. The method is highly targeted, easy to operate, and has lower cost.
[0037] The present invention has the following beneficial effects:
[0038] The ceramic core provided by the present invention comprises a ceramic inner core and an outer core. The distance between the recrystallization positions of the ceramic inner core and the outer core corresponding to the blades is adjusted by the size of the ceramic inner core. When the diameter or thickness of the ceramic inner core is 0.5-2.0 mm, the recrystallization positions of the ceramic inner core and the outer core are spaced 1-5 mm apart, thereby effectively reducing the possibility of recrystallization in the inner cavity. When the mass ratio of calcium silicate, quartz glass powder and cristobalite is 1.0:66.5:30, the diameter of the ceramic inner core is 2 mm and the distance between the recrystallization positions of the ceramic inner core and the outer core is maintained at 1 mm, almost no recrystallization occurs.
[0039] The ceramic inner core preparation method provided by the present invention uses raw materials of 600-mesh calcium silicate, 325-mesh quartz glass powder and 200-mesh quartz, that is, the main material is silicon oxide, and the core removal time will not be increased; the ceramic inner core is infiltrated by a reinforcing agent to enhance the mechanical strength and durability of the ceramic inner core, thereby meeting the performance requirements.
[0040] The ceramic core of the present invention does not need to be trimmed or its structure changed when preparing the ceramic core, thus improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 This is a schematic diagram of a ceramic core obtained in Example 1 in a specific embodiment of the present invention;
[0043] Figure 2 This is a CT scan of the ceramic core obtained in Example 1 in a specific embodiment of the present invention;
[0044] Figure 3 In a specific embodiment of the present invention, a schematic diagram of a ceramic core obtained in Example 2;
[0045] Figure 4 Schematic diagram of the ceramic core obtained in Example 3 in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] Example 1
[0048] Preparation of ceramic core
[0049] 600-mesh calcium silicate, 325-mesh quartz powder and 200-mesh quartz are mixed in a mass ratio of 1.0:66.5:30, and 0.5 wt % of PVA plasticizer and 2 wt % of paraffin are added, and the mixed slurry is obtained by ball milling;
[0050] The mixed slurry is molded by hot pressing process to obtain a blank, the blank has a diameter of 2 mm and a length of 20 mm, and the pressure during the molding process is 2 MPa;
[0051] The green embryo is calcined in a roasting furnace at a temperature of 1450°C for 3 hours to obtain a fired green embryo;
[0052] The fired green body is impregnated with epoxy resin and placed in an oven to be fully dried to obtain a ceramic core.
[0053] Preparing the external core
[0054] The external core is prepared by hot injection molding, and a 2mm diameter extraction needle is set at 1mm corresponding to the recrystallization position in the molding mold, and then the sheet is extracted, and the pressing is completed to form an external core with a hole.
[0055] Preparation of ceramic core
[0056] The ceramic inner core is embedded in the hole reserved in the outer core, and then filled with alumina or silicon oxide ceramic rods to seal the hole. The port position is repaired with a high-temperature adhesive to obtain a ceramic core. The distance between the recrystallization position of the ceramic inner core and the outer core is maintained at 1mm.
[0057] Depend on Figure 1 It can be seen that the schematic diagram of the ceramic core obtained in Example 1 is Figure 2 The CT scan of the ceramic core obtained in Example 1 can be seen.
[0058] Example 2
[0059] Preparation of ceramic core
[0060] 600-mesh calcium silicate, 325-mesh quartz powder and 200-mesh quartz were mixed in a mass ratio of 8.0:20:15, and 1 wt% of PVA plasticizer and 1 wt% of paraffin were added, and the mixed slurry was obtained by ball milling;
[0061] The mixed slurry is molded by hot pressing process to obtain a blank, the blank has a diameter of 0.5 mm and a length of 20 mm, and the pressure during the molding process is 2 MPa;
[0062] The green embryo is calcined in a roasting furnace at a temperature of 1000°C for 8 hours to obtain a fired green embryo;
[0063] The fired green body is impregnated with epoxy resin and placed in an oven to be fully dried to obtain a ceramic core.
[0064] Preparing the external core
[0065] The external core is prepared by hot injection molding, and a drawing needle with a diameter of 0.5 mm is set at the corresponding recrystallization position 5 mm in the molding mold, and then the sheet is drawn out, and the pressing is completed to form an external core with a hole.
[0066] Preparation of ceramic core
[0067] The ceramic inner core is embedded in the hole reserved in the outer core, and then filled with alumina or silicon oxide ceramic rods to seal the hole. The port position is repaired with a high-temperature adhesive to obtain a ceramic core. The distance between the recrystallization position of the ceramic inner core and the outer core is maintained at 5mm.
[0068] Depend on Figure 3 It can be seen that the schematic diagram of the ceramic core obtained in Example 2.
[0069] Example 3
[0070] Preparation of ceramic core
[0071] The raw materials of 500 mesh calcium silicate, 350 mesh quartz glass powder and 150 mesh quartz are mixed in a mass ratio of 4.0:30:25, and then 1wt% PVA plasticizer and 2wt% paraffin are added, and the mixed slurry is obtained by ball milling;
[0072] The mixed slurry is molded by hot pressing process to obtain a blank, the blank has a diameter of 0.5 mm and a length of 20 mm, and the pressure during the molding process is 2 MPa;
[0073] The green embryo is calcined in a roasting furnace at a temperature of 1200°C for 6 hours to obtain a fired green embryo;
[0074] The fired green body is impregnated with epoxy resin and placed in an oven to be fully dried to obtain a ceramic core.
[0075] Preparing the external core
[0076] The external core is prepared by hot injection molding, and a 1mm diameter extraction needle is set at 5mm corresponding to the recrystallization position in the molding mold, and then the sheet is extracted, and the pressing is completed to form an external core with a hole.
[0077] Preparation of ceramic core
[0078] The ceramic inner core is embedded in the hole reserved in the outer core, and then filled with alumina or silicon oxide ceramic rods to seal the hole. The port position is repaired with a high-temperature adhesive to obtain a ceramic core. The distance between the recrystallization position of the ceramic inner core and the outer core is maintained at 2.5 mm.
[0079] Depend on Figure 4 It can be seen that the schematic diagram of the ceramic core obtained in Example 3.
[0080] Example 4
[0081] Preparation of ceramic core
[0082] The raw materials of 600 mesh calcium silicate, 325 mesh quartz glass powder and 200 mesh quartz are mixed in a mass ratio of 1.0:66:30, and then 0.5 wt % of PVA plasticizer and 2 wt % of paraffin are added, and the mixed slurry is obtained by ball milling;
[0083] The mixed slurry is molded by hot pressing process to obtain a blank, the blank has a diameter of 2 mm and a length of 20 mm, and the pressure during the molding process is 2 MPa;
[0084] The green embryo is calcined in a roasting furnace at a temperature of 1450°C for 3 hours to obtain a fired green embryo;
[0085] The fired green body is impregnated with epoxy resin and placed in an oven to be fully dried to obtain a ceramic core.
[0086] Preparing the external core
[0087] The external core is prepared by hot injection molding, and a 2mm diameter extraction needle is set at 1mm corresponding to the recrystallization position in the molding mold, and then the sheet is extracted, and the pressing is completed to form an external core with a hole.
[0088] Preparation of ceramic core
[0089] The ceramic inner core is embedded in the hole reserved in the outer core, and then filled with alumina or silicon oxide ceramic rods to seal the hole. The port position is repaired with a high-temperature adhesive to obtain a ceramic core. The distance between the recrystallization position of the ceramic inner core and the outer core is maintained at 1mm.
[0090] Comparative Example 1
[0091] Preparation of ceramic core
[0092] The ceramic core is prepared by hot pressing process, which is the same as the external core in Examples 1-3 except that no holes are provided, and does not contain an inner core.
[0093] Experimental example
[0094] Recrystallization test was performed on the ceramic core without inner core of Examples 1-3 and Comparative Example 1
[0095] The detection method is to analyze the ceramic cores of Examples 1 to 3 and Comparative Example 1 by visual inspection after heat treatment to obtain the crystallization ratio of the ceramic cores.
[0096] The test results are shown in Table 1 below.
[0097] Table 1 Recrystallization test results
[0098] Leaf Type Core type Inner core Inner core distance Recrystallization ratio Example 1 Guide blade 1 Silicon-based core Yes, φ2.0 1.0mm 0% Example 2 Guide blade 1 Silicon-based core Yes, φ0.5 5.0mm 12.4% Example 3 Guide blade 1 Silicon-based core Yes, φ1.0 2.5mm 13.7% Example 4 Guide blade 1 Silicon-based core Yes, φ2.0 1.0mm 6.7% Comparative Example 1 Guide blade 1 Silicon-based core none / 56.30%
[0099] It can be seen from Table 1 that the recrystallization ratio of the ceramic cores obtained by Examples 1-3 of the present invention is significantly lower than that of the ceramic core in Comparative Example 1, that is, the ceramic cores obtained by Examples 1-3 significantly reduce the recrystallization ratio, achieving the effect of reducing the recrystallization of the inner cavity of the ceramic core.
Claims
1. A powder, characterized in that: The powder material comprises calcium silicate, quartz glass powder and cristobalite, and the mass ratio thereof is (1.0-8.0): (20-66.5): (15-30).
2. The powder according to claim 1, characterized in that: The powder material includes 500-600 mesh calcium silicate, 325-350 mesh quartz glass powder and 150-200 mesh quartz.
3. The powder according to claim 1, characterized in that: The mass ratio of calcium silicate, quartz glass powder and cristobalite is (2.0-6.0):(30-40):(20-25).
4. The powder according to claim 1, characterized in that: The mass ratio of calcium silicate, quartz glass powder and cristobalite is 1.0:66.5:
30.
5. A ceramic core for reducing recrystallization in the inner cavity of a single crystal blade, characterized in that: Made from the powder according to any one of claims 1 to 4.
6. The ceramic inner core according to claim 5, characterized in that: The ceramic inner core is a slender rod-shaped ceramic inner core with a diameter of 0.5-2 mm, or a sheet-shaped ceramic inner core with a thickness of 0.5-2 mm.
7. A method for preparing a ceramic core for reducing recrystallization in a single crystal blade cavity, comprising the following steps: Mixing the powder according to any one of claims 1 to 4 with an additive, grinding and obtaining a mixed slurry, wherein the additive comprises a plasticizer; The mixed slurry is formed into a ceramic core blank, and the forming method includes: hot pressing method, dry pressing method or extrusion molding method; Sintering the ceramic inner core blank to obtain a sintered ceramic inner core blank; The sintered ceramic core blank is immersed in a reinforcing agent and then dried to obtain a ceramic core.
8. The preparation method according to claim 7, characterized in that: The ceramic core blank is sintered in an air environment, and the sintering process is: heating from room temperature to 1000-1450° C., and maintaining the temperature for 3-8 hours.
9. A ceramic core for reducing recrystallization in the inner cavity of a single crystal blade, comprising the ceramic inner core described in claim 5 or 6 or a ceramic inner core obtained by the preparation method described in any one of claims 4 to 8, and an external core compatible with the ceramic inner core.
10. The ceramic core according to claim 9, wherein the outer core is provided with a hole for placing the ceramic inner core, and the distance between the ceramic inner core and the outer core corresponding to the blade position is adapted to the size of the ceramic inner core; The diameter or thickness of the ceramic inner core is 0.5-2 mm, and the distance between the ceramic inner core and the corresponding blades of the outer core is 1-5 mm.
